2013
DOI: 10.1089/ars.2012.4999
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Reactive Oxygen Species Profile Confers Chemoresistance in Glioma-Propagating Cells and Associates with Patient Survival Outcome

Abstract: Gliomas are notoriously recurrent and highly infiltrative, and have been shown to arise from stem-like cells. We implicate an elevated O2(-):H2O2 ratio as a prosurvival signal in GPC self-renewal and proliferation. The ROS Index provides quantification of O2(-):H2O2-mediated chemosensitivity, an advancement in a previously qualitative field. Intriguingly, glioma patients with a reduced ROS Index correlate with longer survival and the Proneural molecular classification, a feature frequently associated with tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…Furthermore, persistent elevation of ROS, in particular O 2 •− , has been implicated in enhanced resistance in glioma propagating cells. Koh and colleagues demonstrated that the ratio of O 2 •− to H 2 O 2 dictated the sensitivity of those cells [63]. Depletion of this ratio, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, persistent elevation of ROS, in particular O 2 •− , has been implicated in enhanced resistance in glioma propagating cells. Koh and colleagues demonstrated that the ratio of O 2 •− to H 2 O 2 dictated the sensitivity of those cells [63]. Depletion of this ratio, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of this ratio, i.e. increase in H 2 O 2 levels, rendered these cells sensitive to drug-induced apoptosis [63]. Therefore, our strategy to increase intracellular H 2 O 2 levels by MnBuOE, enabling its cell death-promoting catalytic actions, may be advantageous as it can potentially target glioma stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…The screening results in a list of compounds with a highly correlating gene expression pattern to that of the phenotype of interest, which has the potential to aid in finding a novel treatment for a disease or to identify novel pathways or genes involved in a complex biological process. To date, the CMap has been successfully used to identify compounds and combination therapies that show promise in the treatment of osteoarthritic pain (5), adenocarcinoma (6), kidney disease (7), gliomas (8), and NK cell neoplasms (9).…”
mentioning
confidence: 99%
“…confers a survival advantage, while a significant shift toward H 2 O 2 creates a permissive environment for death execution (84,144). For example, H 2 O 2 is known to suppress Wnt/b-catenin signaling, an important survival and growth pathway, through a variety of mechanisms, including targeting the interaction between nucleoredoxin and disheveled (Dvl) (52) and via oxidative modification of the zinc-coordinating cysteines of tankyrase resulting in its inactivation (78).…”
Section: Reactive Oxygen Species and Their Role In Cell Signalingmentioning
confidence: 99%